Neutrophil migration towards C5a and CXCL8 is prevented by non‐steroidal anti‐inflammatory drugs via inhibition of different pathways. (July 2014) - Bertolotto, Maria; Contini, Paola; Ottonello, Luciano; Pende, Aldo; Dallegri, Franco; Montecucco, Fabrizio
<x xml:space="preserve">Abstract</x> Background and Purpose Non‐steroidal anti‐inflammatory drugs (NSAIDs) have been shown to induce PG‐independent anti‐inflammatory actions. Here, we investigated the role of three different NSAIDs (naproxen, ibuprofen and oxaprozin) on neutrophil responses to CXCL8 and C5a. Experimental Approach Human neutrophils were isolated from healthy volunteers by dextran and Ficoll‐Hypaque density gradients. Neutrophils were pre‐incubated with different concentrations (1–100 µM) of NSAIDs or kinase inhibitors. Neutrophil degranulation into supernatants was tested by elisa and zymography. Neutrophil chemotaxis was determined using Boyden chambers. F‐actin polymerization was determined by Alexa‐Fluor 488‐conjugated phalloidin fluorescent assay. Integrin expression was assessed by flow cytometry. The phosphorylation of intracellular kinases was studied by Western blot. Key Results Pretreatment with NSAIDs did not affect neutrophil degranulation, but inhibited neutrophil migration and polymerization of F‐actin, in response to CXCL8 and C5a. Pretreatment with different NSAIDs prevented C5a‐induced integrin (CD11b) up‐regulation, while only ibuprofen reduced CXCL8‐induced CD11b up‐regulation. Pre‐incubation with naproxen or oxaprozin, but not ibuprofen, inhibited the PI3K/Akt‐dependent chemotactic pathways. Both endogenous (released in cell supernatants) or exogenous (added to cell cultures) PGE2 did not affect C5a‐ or CXCL8‐induced activities. Short‐term incubation with NSAIDs did not affect neutrophil PGE2 release. Conclusion and Implications Treatment with NSAIDs reduced C5a‐ and CXCL8‐induced neutrophil migration and F‐actin polymerization via different mechanisms. Inhibition by ibuprofen was associated with integrin down‐regulation, while naproxen and oxaprozin blocked the PI3K/Akt pathway. Both NSAID actions were independent of COX inhibition and PGE2 release.